The diversity of Triassic South American sphenodontians: a new basal form, clevosaurs, and a revision of rhynchocephalian phylogeny - Chambi Trowell, Sofia A. V. (2021)
Rhynchocephalians are a group of lizard-like diapsid reptiles that were very diverse during the Mesozoic but are now restricted to a single extant genus in New Zealand. Recent cladistic analyses have revealed two major clades, Eusphenodontia and the more crownward Neosphenodontia, but relationships of individual taxa have remained difficult to determine because of missing data and an unrevised data matrix. Here we drastically revise the established data matrix on rhynchocephalians by reassessing, evaluating, and adding new characters and operational taxonomic units, differing from any previous analyses in our goal to consider all known rhynchocephalians. In addition, we describe a new genus and species of an early eusphenodontian taxon from the Norian of southern Brazil, with a unique mosaic of plesiomorphic and apomorphic traits, and we re-examine the craniodental anatomy of the eusphenodontian Clevosaurus brasiliensis with µCT imaging, revealing a unique form of acrodonty amongst rhynchocephalians.